2006
DOI: 10.1111/j.1365-2257.2006.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Bernard-Soulier syndrome in pregnancy

Abstract: Bernard-Soulier syndrome (BSS) is a rare autosomal recessively inherited bleeding disorder. Pregnancy in patients with BSS is characterized by ante-, intra-, or postpartum haemorrhage, which may be delayed and severe. There is no consensus in the management of BSS in pregnancy and so far only 16 pregnancies in nine patients have been described. We report a further three pregnancies in two women with the syndrome. We also outline our management of pregnant patients with BSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 24 publications
0
35
0
1
Order By: Relevance
“…The reports dated from 1976 [25] to 2010 [26], and the age of patients ranged from 16 to 39 years [27,28]. The majority of the cases reported management of postpartum hemorrhage with tranexamic acid [29,30,27,[31][32][33][34][35][36][37]26]. Seven studies reported antepartum hemorrhage [25,[38][39][40][41][42][43].…”
Section: Case Reportsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reports dated from 1976 [25] to 2010 [26], and the age of patients ranged from 16 to 39 years [27,28]. The majority of the cases reported management of postpartum hemorrhage with tranexamic acid [29,30,27,[31][32][33][34][35][36][37]26]. Seven studies reported antepartum hemorrhage [25,[38][39][40][41][42][43].…”
Section: Case Reportsmentioning
confidence: 99%
“…Seven studies reported antepartum hemorrhage [25,[38][39][40][41][42][43]. Hemorrhage associated with hematological disorders was reported in nine cases [44,29,30,31,28,[33][34][35][36][37]. The most common hematological disorder mentioned was Bernard Soulier syndrome [29,[34][35][36], followed by hemophilia [30,33], leukemia [28], other platelet disorders such as Glanzmann's thrombasthenia [44], Evan's syndrome [31], and platelet storage pool disease [37].…”
Section: Case Reportsmentioning
confidence: 99%
See 3 more Smart Citations